Siva’s Demon Devotee: Karaikkal Ammaiyar - Paykattu, Vinoy (Journal of Dharma, 2010)
Elaine Craddock, Siva’s Demon Devotee: Karaikkal Ammaiyar, Albany: State University of New York Press, 2010, pages xii + 193; ISBN: 978-14384-3087-4.